Dopaminergic dysfunction in neuropsychiatric disorders. Pathophysiology, current therapeutics, and future perspectives - Chanda, Chandrasekhar; Surepalli, Sobhitha (Neuropsychiatria i Neuropsychologia/Neuropsychiatry and Neuropsychology, 2019)
Dopaminergic signalling is crucial for a variety of brain functions, and abnormal dopamine regulation leads to neuropsychiatric disorders. Dopamine (DA) receptors are members of the G protein-coupled receptors (GPCRs) superfamily, with seven transmembrane spanning domains. DA, upon release from pre-synaptic neurons, activates dopamine receptor subtypes D1 to D5 and induces Gs/olf- and Gi/o-mediated intracellular signalling. Defects in DA signalling cause either over-activation or dysfunction of DA regulation, leading to major psychiatric and neurological disorders, including Parkinson’s, schizophrenia, attention deficit with hyperactivity disorder, and bipolar disorder. Molecules that act as antagonists/agonists on D2/D3 receptors have been used clinically to treat many neuropsychiatric and neurodegenerative disorders. Most of the anti-psychotic drugs in use are primarily based on D2 receptor antagonism and serotonin receptor antagonism. However, antipsychotic drugs were developed 50 years ago, and the efficacy of these drugs has not been refined/upgraded very much. Thus, there is a great need to develop novel therapeutic strategies in designing/discovering a newer class of drugs. This can be achieved by having a better understanding about DA regulation and dopaminergic signalling in neuropsychiatric disorders. The in silico approach can be a tool for studying DA receptors and other protein targets involved in dopaminergic signalling. Utilising the existing knowledge on DA signalling in combination with various in silico approaches can be helpful in designing new chemical entities (NCEs). This review focuses on receptor functioning and dopaminergic signalling in major neuropsychological disorder, current therapeutic strategies, and future perspectives.